Factors Associated with Musculoskeletal Disorders among Registered Nurses: Evidence from the Thai Nurse Cohort Study - Thinkkhamrop, W.; Laohasiriwong, W. (Kathmandu University Medical Journal, 2017)
Background Health, safety, and well being have been known to be influenced by occupational characteristics. Nurses constantly encounter musculoskeletal disorders (MSDs) from work demands worldwide. Nevertheless, there is insufficient of knowledge regarding causes of musculoskeletal disorders among nurses in Thailand.Objective To investigate factors associated with musculoskeletal disorder among registered nurses in Thailand.Method This study is part of the 2009 Thai Nurse Cohort Study which consisted of 18,756 nationally representative sample of registered nurses. Data collection was performed via postal self-administered questionnaires. Manifesting musculoskeletal disorders was self-reported by registered nurses, 1,070 nurses were excluded since they were unemployed during previous 12 months. Multiple logistic regression was used for data analysis.Result Of 17,686 registered nurses, the overall 12 months prevalence of musculoskeletal disorders was 47.8%. It was found that workplace violence was the strongest factor which statistically significant associated with musculoskeletal disorders (adjusted odds ratio, OR, 2.01; 95% confidence interval, 95% CI, 1.42 to 2.83; P < 0.001), anxiety/depression (OR = 1.96: 95% CI: 1.78 to 2.15; P < 0.001), perceiving job required a lot of physical effort (OR = 1.69; 95% CI: 1.52 to 1.87; P < 0.001), every 10 years increased of age (OR = 1.40; 95% CI: 1.22 to 1.62; P < 0.001), overweight (OR = 1.39; 95% CI: 1.01 to 1.52; P = 0.015).Conclusion Registered nurses were most vulnerable of musculoskeletal disorders especially those who experienced workplace violence, anxiety/depression, strenuous work, older age, and overweight. Consequently, recommending safety practices to nurses should be considered for musculoskeletal disorders (MSDs) prevention by ergonomics and workplace design.